2012
DOI: 10.1186/1475-2875-11-368
|View full text |Cite
|
Sign up to set email alerts
|

Exploring health providers’ and community perceptions and experiences with malaria tests in South-East Nigeria: a critical step towards appropriate treatment

Abstract: BackgroundThe adoption of ACT as the first line treatment for uncomplicated malaria in Nigeria has concentrated attention on the role of testing in appropriate malaria treatment. There are calls at both national and global level for malaria treatment to be based on test result, but it is still unclear how testing can be incorporated into treatment-seeking and practices of health providers. This study explored community members and health providers’ perceptions and experiences with malaria tests in south east N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 23 publications
1
40
1
Order By: Relevance
“…[44][45][46][47] Results of the individual trials were disseminated to IQR=interquartile range. *Proportion of patients testing positive for malaria (among those in intervention settings who were tested) presented as proxy for malaria epidemiology.…”
Section: Patient Involvementmentioning
confidence: 99%
“…[44][45][46][47] Results of the individual trials were disseminated to IQR=interquartile range. *Proportion of patients testing positive for malaria (among those in intervention settings who were tested) presented as proxy for malaria epidemiology.…”
Section: Patient Involvementmentioning
confidence: 99%
“…This is similar to the situation in Nigeria, in which nearly 60% of Nigerians seek treatment for malaria at drug shop outlets in the private health sector, composed of licensed community pharmacies (or referred to as pharmacies) and loosely regulated proprietary and patent medicine vendors (PPMV) [15, 28, 29]. This treatment-seeking behaviour is attributed to patients’ convenience, availability of familiar drugs, affordability, reduced waiting hour and proximity [30]. …”
Section: Introductionmentioning
confidence: 56%
“…Other studies have similarly reported less-than-optimal coverage of diagnostic tests (Hamer et al 2007;Nyandigisi et al 2011;Masanja et al 2012). In addition to poor diagnostic availability (Ezeoke et al 2012), reasons for poor coverage may include inadequate health worker training, negative health worker perceptions of mRDTs, provider workload or patient preferences (Chandler et al 2008a;Williams et al 2008;Asiimwe et al 2012;Baiden et al 2012). Health centre and dispensary patients paid a flat rate for treatment, so patient willingness-to-pay for tests is not expected to have been a factor in these facilities, but may have contributed in hospital settings where separate fees were sometimes charged for diagnostics.…”
Section: Discussionmentioning
confidence: 97%
“…; Ezeoke et al . ). While some studies have reported poor compliance with negative test results (Hamer et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation